Visual intelligence : perception, image, and manipulation in visual communication - Barry, Ann Marie (State University of New York Press, 1997)
Today, our environment is dominated by the visual. This book explores "visual intelligence" as a basic and indispensable tool of cultural survival. The author offers a practical manual on a non-superficial level for those who seriously want to know how images are processed, how they function in relation to our innermost beings, and how they form the psychological fabric of our political, social, and economic environment. Barry defines how we derive meaning from images and examines perceptual process, how it has evolved, and the role it plays in our thinking. She critically examines the concept of rationality and explores how visual logic works to create meaning. The book goes behind the obvious and beyond the superficial as it critically examines the visual power and logic of images, cutting across a variety of areas: perceptual psychology, art, television, film, literature, advertising, and politics